Deixis in Inside Sumatera Magazine - Rafina Rafina; Johan Sinulingga (LINGUISTICA, 2013)
ABSTRACT This study attempts to investigate deixis found in the articles of Inside Sumatera Magazine, especially in Adventure, Destination and Travelling coloums. It was conducted to discover the types of deixis as proposed by Cruse (2000) namely: person deixis, place deixis, time deixis, discourse deixis, and social deixis. The objectives of this study is to describe type of deixis and to find out the most dominant type of deixis in articles of Inside Sumatera magazine. This study was taken from the article of Inside sumatera magazine and ten article are taken as the samples. Documentary technique is due in collecting data. The findings show that the total number of deixis from the whole articles were 1504 occurrences, 656 occurrences (43.62%) was person deixis, 465 occurrences (30.92%) was place deixis, 227 occurrences (15.09%) was time deixis, 137 occurrences (9.10%) was discourse deixis, and 19 occurrences (1.27%) was social deixis. Person deixis is the dominant type used in those article (43.62%). Keywords: Deixis, person deixis, place deixis, time deixis, discourse deixis, social deixis, inside sumatera, magazine.